1996
DOI: 10.1103/physrevb.54.11752
|View full text |Cite
|
Sign up to set email alerts
|

Brownian motion and shape fluctuations of single-layer adatom and vacancy clusters on surfaces: Theory and simulations

Abstract: In recent observations of Brownian motion of islands of adsorbed atoms and of vacancies with mean radius R, the cluster diffusion constant D c varies as R Ϫ1 and R Ϫ2 . From an analytical continuum description of the cluster's steplike boundary, we find a single Langevin equation for the motion of the cluster boundary, rather than three special cases. From this we determine D c and the correlation function G sh for fluctuations of the shape around an assumed equilibrium circular shape. In three limiting cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
129
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 54 publications
10
129
1
Order By: Relevance
“…In that sense, this model would not be able to describe growing cell colonies, precisely because it assumes spurious rigidity of bulk cells. On the other hand, it would be better suited to describe the radial growth of crystalline structures [51]. We have also found that reparametrization invariance as defined in [22] implicitly implies dilatation dynamics.…”
Section: Discussionmentioning
confidence: 92%
“…In that sense, this model would not be able to describe growing cell colonies, precisely because it assumes spurious rigidity of bulk cells. On the other hand, it would be better suited to describe the radial growth of crystalline structures [51]. We have also found that reparametrization invariance as defined in [22] implicitly implies dilatation dynamics.…”
Section: Discussionmentioning
confidence: 92%
“…Despite the usefulness of the Cartesian representation in many cases, there are some growth profiles that can not be described according to it. Physical settings such as fluid flow in porous media [1], grain-grain displacement in Hele-Shaw cells [2], fracture dynamics [3], adatom and vacancy islands on crystal surfaces [4], and atomic ledges bordering crystalline facets [5,6] present interfaces that violate the hypothesis of the Cartesian representation. Biological systems are also characterized by an approximate spherical symmetry: bacterial colonies [7], fungi [8], epithelial cells [9], and cauliflowers [10] develop rough surfaces which are not describable from a planar reference frame.…”
Section: Introductionmentioning
confidence: 99%
“…Since the origin of the coordinate system can be chosen freely, we define it at any time in such a way that it coincides with the center of mass of the cluster. If we define the function R͑u͒ as the time-averaged position of the cluster's edge relative to its center of mass, we may describe the deviation from the average shape in terms of a dimensionless variable g͑u, t͒ [15]:…”
Section: (Received 25 September 1998)mentioning
confidence: 99%
“…To quantify the shape fluctuations, we follow the work of Khare and Einstein [15] and define the instantaneous position of the cluster edge in cylindrical coordinates by a function r͑u, t͒, where r and u are the radius and polar angle, respectively, and t is the time. Since the origin of the coordinate system can be chosen freely, we define it at any time in such a way that it coincides with the center of mass of the cluster.…”
Section: (Received 25 September 1998)mentioning
confidence: 99%